Technology-Mediated Translanguaging for Environmental Meaning-Making in Asynchronous ESP Vocational Discussion Forums - Ira Mutiaraningrum; Nur Hafiz Abdurahman; Arif Nugroho; Sri Lestari; Made Wahyu Mahendra; Sulaiman (ELE Reviews: English Language Education Reviews, 2026)
Although studies have explored translanguaging in multilingual classrooms, an investigation into how translanguaging operates in asynchronous digital learning environments, particularly in vocational ESP contexts, is still limited. This study examines how translanguaging practices are applied in English for Specific Purposes (ESP) online discussion forums in vocational agribusiness English courses. The study uses an interpretive approach to explore how multilingual language practices support meaning-making when students engage with environmental issues relevant to their field. The study involved third-year Agribusiness students from a vocational college, and data were collected from excerpts of students’ asynchronous discussions related to agribusiness, deforestation, mining activities, and environmental risks in an English course. Of the 24 3rd-semester students who participated in the online discussion forum, 81 comments were analyzed. Notably, data collection coincided with significant flooding in Sumatra, Indonesia, which became a recurring point of reference in student interactions. Using thematic analysis, this study explicitly reveals three interrelated discursive patterns in students’ environmental reasoning facilitated by translanguaging: problem identification, causal explanation, and proposed strategies. Findings from the open-ended questionnaire also showed that students considered that using a single language alone was not enough to discuss complex agribusiness topics, so they translanguaged to explain technical concepts, connect ideas, and convey opinions more clearly.